Mixed-Method Evaluation of the Public Health Questionnaire for Estimating Depression Among Tibetan Buddhist Monastics - Mascaro, Jennifer S.; Shellman, Danielle; Keaton, Wesley A.; Willson, Madison; Brauer, Erin; Samphel, Tsondue; Chang, Hope; Raison, Charles L.; Zivot, Joel; Eisen, Arri (Frontiers in Communication, 2021)
Background: Depression is the largest source of global medical disability, highlighting the importance of translating and validating depression screening instruments to improve our understanding of differences in the prevalence of depression in divergent cultures around the world. The aim of this study was to translate and evaluate a widely used depression screening and diagnostic instrument, the Patient Health Questionnaire-9 (PHQ-9), for use with Tibetan populations. A secondary aim was to use the Tibetan-PHQ-9 (T-PHQ-9) to estimate the prevalence of depression symptoms in a population of Tibetan-speaking Buddhist monastic scholars engaging in a 6-year science curriculum in India, the Emory Tibet Science Initiative (ETSI). Methods: Three-hundred-eighty-four monastics (363 monks, 21 nuns) completed the T-PHQ-9. We computed measures of internal consistency and conducted factor analysis to evaluate scale performance. Following this, we evaluated the prevalence of depressive symptoms among the monastic population. We also conducted cognitive interviews with 6 monastics to explore their thought processes when completing the instrument and when thinking about depression symptoms. Results: The T-PHQ-9 had acceptable reliability and demonstrated a single-factor structure. While having low energy was the most commonly endorsed symptom, monastics did not have overall higher endorsement rates of other somatic symptoms when compared with endorsement rates of emotional symptoms. Over 10% of the monastics scored in the moderately severe to severe range and met criteria for major depressive disorder (MDD), using standard diagnostic criteria cut-offs. First year monks had the highest mean score, and there was not a significant difference between monks and nuns. Cognitive interviews revealed some variation in the cognitive processes used to complete the instrument, particularly with symptoms related to energy and concentration. Conclusion: These preliminary findings indicate that the Tibetan PHQ-9 is a reliable instrument for assessing depressive symptoms, as evidenced by its ability to inform how symptoms are experienced, interpreted, and communicated among Buddhist monastics. Results from the cognitive interviews may be important for further refining the instrument.